Fatherhood Reflected In Danielle Steel's Winners Novel(2013): A Humanistic Psychological Approach - ISTIYANTI, ISTIYANTI; , Dr. Phil. Dewi Candraningrum, M.Ed (2016)
The major problem of this study is fatherhood. How a father shows his love to his lovely daughter. The objective of this study is to analyze this novel based on humanistic approach. The writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is Winners novel by Danielle Steel. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major character is a fatherhood. It is proven by a father, Bill Thomas. Bill has a child, her name is Lily Thomas. Lily is a smart, energic and stromg girl. Bill loved Lily so much. Bill wants the best things for Lily. Lily can fulfill the five basic needs by Abraham Maslow (Physiological needs, safety needs, belongingness and love needs, estem needs, and self-actualization needs).